The hallmarks of CMV-specific CD8 T-cell differentiation. - Van Den Berg, S; Pardieck, I; Lanfermeijer, J; Sauce, D; Klenerman, P; Van Baarle, D; Arens, R (Springer, 2019)
Upon cytomegalovirus (CMV) infection, large T-cell responses are elicited that remain high or even increase over time, a phenomenon named memory T-cell inflation. Besides, the maintained robust T-cell response, CMV-specific T cells seem to have a distinctive phenotype, characterized by an advanced differentiation state. Here, we will review this "special" differentiation status by discussing the cellular phenotype based on the expression of CD45 isoforms, costimulatory, inhibitory and natural killer receptors, adhesion and lymphocyte homing molecules, transcription factors, cytokines and cytotoxic molecules. In addition, we focus on whether the differentiation state of CMV-specific CD8 T cells is unique in comparison with other chronic viruses and we will discuss the possible impact of factors such as antigen exposure and aging on the advanced differentiation status of CMV-specific CD8 T cells.